PELABELAN GRACEFUL GANJIL PADA GRAF DUPLIKASI DAN SPLIT BINTANG - Bantara, J A; Sudarsana, I W; Musdalifah, S (Program Studi Matematika, Universitas Tadulako, 2018)
Graph is not an empty a finite of the objects that called point (vertex) with the couple was not that is the side (edge). The set point denoted by , while the set edge denoted by . Odd graceful labeling on graph with side is a function injective from so that induced function such that in label with so label sides would be different. A graph that have an odd graceful labeling is called odd graceful graph. The result showed that duplicate star graph for and split star graph for , for even satisfie odd graceful labeling.